Discrete Isolation and Continuous Area Drive Genetic Divergence Across Mediterranean Islands - Leonardo Dapporto; Claudia Bruschini; Adele Bordoni; Alessandro Cini; Vlad Dincă; Luca Di Nuzzo; Alessio Iannucci; Mattia Menchetti; Lorenzo Pasquali; Vania Salvati; Loukia Spilani; Gerard Talavera; et al. (Global Ecology and Biogeography, 2026)
Aim Comparison between islands and equivalent mainland areas to dissect the effect of area, isolation and species traits in determining island genetic endemicity and genetic differentiation. Location The Western Mediterranean region. Time Period Current. Major Taxa Studied Butterflies (Lepidoptera, Papilionoidea). Methods We analysed 10,367 COI sequences from 105 species, 34 islands and 47 sea straits, along with four functional species traits. We compared determinants of genetic diversity (nucleotide diversity, NucDiv ), endemic mutations (EM) and the Dst fixation index between island populations and similarly sized mainland populations (Continental Area Equivalents, CAEs). Generalised linear mixed models tested fixed effects and interactions of island characteristics and species traits. We also evaluated whether population‐level effects (individual species increasing differentiation with island size and isolation) or community‐level effects (larger, less isolated islands hosting more genetically divergent species) better explain observed island patterns. Results CAEs and islands exhibited highly distinct genetic signatures. NucDiv was higher in CAEs while Dst was higher across sea straits than between land areas separating CAEs, particularly for larger islands and non‐migratory species. EM increased with island area, especially in non‐migratory and small species. Island communities were significantly nested. Widespread species also showed lower genetic variation, thus producing a strong community‐level effect. The population‐level effects showed a weaker effect. Counterintuitively, increasing isolation did not increase divergence, as both processes tended to reduce genetic differentiation in more isolated islands. Main Conclusions Comparing islands with CAEs reveals that even narrow sea barriers of a few kilometres greatly reduce gene flow in non‐migratory butterflies, increasing genetic differentiation to a greater extent than similar mainland distances. After controlling for the presence of sea straits, island size predicts genetic divergence while increasing isolation does not. Overall, endemicity remains low, indicating that mainland‐driven genetic turnover, rather than in situ evolution, dominates insular genetic patterns.

Ecotoxicity of bioinsecticides to social wasps - Livia De Fazi; Needhi K. Thangasamy; Angelo Canale; Alessandro Cini; Giovanni Benelli (Current Opinion in Environmental Science & Health, 2024)

What’s in the bee nest holes? A single aggregation of Megachile parietina reveals and helps to fill up Eltonian shortfalls - Elisa Monterastelli; Alfonso Orlotti; Giulia Calderai; Chiara Natali; Marta Mariotti Lippi; Claudio Ciofi; Alessandro Cini; Leonardo Dapporto; Marino Quaranta; Francesca Romana Dani (Journal of Insect Conservation, 2024)
Megachile (Chalicodoma) parietina (Geoffroy, 1785) is a Palearctic solitary bee included in the Red List of some central European Countries. Females build durable nests, reused year after year, by mixing soil with a salivary secretion. Like for most solitary bees, the resources contained within M. parietina nests attract several other insects which exploit pollen supplies or feed on the immature brood. These associated insects have mainly been studied for mantained bees and considered for their effect on the host reproductive success. A very large nesting aggregation of M. parietina in Central Tuscany has been studied for three consecutive years. We have identified 32 associated insect species, which certainly are an underestimate of the species present. Among the identified species, only eight had been previously reported for M. parietina . All the species were classified both according to the specificity for the host taxon ( Chalicodoma , Megachilidae, Anthophila, Hymenoptera, Others) and to the ecological relationship (cleptoparasites, parasitoids, predators of larvae, food commensal, scavengers, and occasional nest users). This highlighted both the richness of the ecological network within the nesting aggregation and the value of studying these nesting sites to fill Eltonian shortfalls, i.e. the deficiency in ecology knowledge, of bees and their associated fauna. Implications for insect conservation. We suggest that, besides their role in pollination, large and stable bee nesting sites increase the local insect biodiversity, and that attention should be paid to their conservation within actions aimed to support populations of wild pollinators.

Unstructured citizen science reduces the perception of butterfly local extinctions: the interplay between species traits and user effort - Elia van Tongeren; Ginevra Sistri; Marco Bonifacino; Mattia Menchetti; Lorenzo Pasquali; Vania Salvati; Emilio Balletto; Simona Bonelli; Alessandro Cini; Mariagrazia Portera; Leonardo Dapporto (Biodiversity and Conservation, 2023)
The detection of local extinctions is often hindered by the lack of long-term monitoring schemes, and thus relies on time series of presence data. Recently, citizen science has repeatedly shown its value in documenting species occurrences. We investigated the effectiveness of unstructured citizen science records in reducing the perception of local extinctions in butterfly populations across Italian National Parks. We addressed three research questions: (i) the ability of citizen science data to supplement existing knowledge to complete time series of occurrences, (ii) the impact on data collection of three species features (species size, distribution and length of flight period) determining their appearance, and (iii) the interplay between participant effort and species appearance in the amount of diversity recorded on the iNaturalist platform. Our analysis of 98,922 records of Italian butterflies (39,929 from literature and 58,993 from iNaturalist of which 7427 from National Parks) showed that the addition of iNaturalist data filled many recent gaps in time series, thus reducing the perception of potential local extinctions. Records from more engaged users encompassed a higher fraction of local biodiversity and were more likely to reduce the perception of local extinctions. User effort strongly interacted with species features in determining the frequency of records for individual species. In particular, more engaged users were less affected by species size. We provided updated butterfly checklists for Italian National Parks and a R package to calculate potential extinction upon time series. These results offer guidance for protected areas, conservationists, policymakers, and citizen scientists to optimize monitoring of local populations.

Two ways to be endemic. Alps and Apennines are different functional refugia during climatic cycles - Mattia Menchetti; Gerard Talavera; Alessandro Cini; Vania Salvati; Vlad Dincă; Leonardo Platania; Simona Bonelli; Emilio Balletto; Roger Vila; Leonardo Dapporto (Molecular Ecology, 2021)
Endemics co‐occur because they evolved in situ and persist regionally or because they evolved ex situ and later dispersed to shared habitats, generating evolutionary or ecological endemicity centres, respectively. We investigate whether different endemicity centres can intertwine in the region ranging from Alps to Sicily, by studying their butterfly fauna. We gathered an extensive occurrence data set for butterflies of the study area (27,123 records, 269 species, in cells of 0.5 × 0.5 degrees of latitude‐longitude). We applied molecular‐based delimitation methods (GMYC model) to 26,557 cytochrome c oxidase subunit 1 (COI) sequences of Western Palearctic butterflies. We identified entities based on molecular delimitations and/or the checklist of European butterflies and objectively attributed occurrences to their most probable entity. We obtained a zoogeographic regionalisation based on the 69 endemics of the area. Using phylogenetic ANOVA we tested if endemics from different centres differ from each other and from nonendemics for key ecological traits and divergence time. Endemicity showed high incidence in the Alps and Southern Italy. The regionalisation separated the Alps from the Italian Peninsula and Sicily. The endemics of different centres showed a high turnover and differed in phylogenetic distances, phenology and distribution traits. Endemics are on average younger than nonendemics and the Peninsula‐Sicily endemics also have lower variance in divergence than those from the Alps. The observed variation identifies Alpine endemics as paleoendemics, now occupying an ecological centre, and the Peninsula‐Sicily ones as neoendemics, that diverged in the region since the Pleistocene. The results challenge the common view of the Alpine‐Apennine area as a single “Italian refugium”.

Host plant selection and differential survival on two Aristolochia L. species in an insular population of Zerynthia cassandra - Alessandro Cini; Adele Bordoni; Gea Ghisolfi; Lorenzo Lazzaro; Leonardo Platania; Lorenzo Pasquali; Riccardo Negroni; Fulvia Benetello; Andrea Coppi; Franca Zanichelli; Leonardo Dapporto (Journal of Insect Conservation, 2019)

WASP nest: a worldwide assessment of social Polistine nesting behavior - Sara E. Miller; Sarah E. Bluher; Emily Bell; Alessandro Cini; Rafael Carvalho da Silva; André Rodrigues de Souza; Kristine M. Gandia; Jennifer Jandt; Kevin Loope; Amanda Prato; Jonathan N. Pruitt; David Rankin; et al. (Ecology, 2018)
Cooperative breeding decreases the direct reproductive output of subordinate individuals, but cooperation can be evolutionarily favored when there are challenges or constraints to breeding independently. Environmental factors, including temperature, precipitation, latitude, high seasonality, and environmental harshness have been hypothesized to correlate with the presence of cooperative breeding. However, to test the relationship between cooperation and ecological constraints requires comparative data on the frequency and variation of cooperative breeding across differing environments, ideally replicated across multiple species. Paper wasps are primitively social species, forming colonies composed of reproductively active dominants and foraging subordinates. Adult female wasps, referred to as foundresses, initiate new colonies. Nests can be formed by a single solitary foundress (noncooperative) or by multiple foundress associations (cooperative). Cooperative behavior varies within and among species, making paper wasps species well suited to disentangling ecological correlates of variation in cooperative behavior. This data set reports the frequency and extent of cooperative nest founding for 87 paper wasp species. Data were assembled from more than 170 published sources, previously unpublished field observations, and photographs contributed by citizen scientists to online natural history repositories. The data set includes 25,872 nest observations and reports the cooperative behavioral decisions for 45,297 foundresses. Species names were updated to reflect modern taxonomic revisions. The type of substrate on which the nest was built is also included, when available. A smaller population‐level version of this data set found that the presence or absence of cooperative nesting in paper wasps was correlated with temperature stability and environmental harshness, but these variables did not predict the extent of cooperation within species. This expanded data set contains details about individual nests and further increases the power to address the relationship between the environment and the presence and extent of cooperative breeding. Beyond the ecological drivers of cooperation, these high‐resolution data will be useful for future studies examining the evolutionary consequences of variation in social behavior. This data set may be used for research or educational purposes provided that this data paper is cited.

Effects of trap baits and height on stag beetle and flower chafer monitoring: ecological and conservation implications - Marco Bardiani; Massimiliano Tini; Giuseppe M. Carpaneto; Paolo Audisio; Elisabetta Bussola; Alessandro Campanaro; Alessandro Cini; Emanuela Maurizi; Franco Mason; Giuseppino Sabbatini Peverieri; Pio Federico Roversi; Ilaria Toni; et al. (Journal of Insect Conservation, 2017)

Sterile Rhynchophorus ferrugineus males efficiently impair reproduction while maintaining their sexual competitiveness in a social context - Giuseppe Mazza; Alberto Francesco Inghilesi; Gianluca Stasolla; Alessandro Cini; Rita Cervo; Claudia Benvenuti; Valeria Francardi; Massimo Cristofaro; Silvia Arnone; Pio Federico Roversi (Journal of Pest Science, 2016)

Almost royal: incomplete suppression of host worker ovarian development by a social parasite wasp - Alessandro Cini; Rachele Nieri; Leonardo Dapporto; Thibaud Monnin; Rita Cervo (Behavioral Ecology and Sociobiology, 2014)

Safety aspects of iodinated contrast media related to their physicochemical properties: a pharmacoepidemiology study in two Tuscany hospitals - Francesco Lapi; Enrica Cecchi; Claudio Pedone; Francesco Attanasio; Grazia Banchelli; Alfredo Vannacci; Marina Di Pirro; Martina Moschini; Valentina Berni; Rosanna Matucci; Elisabetta Cini; Antonino Scalia; et al. (European Journal of Clinical Pharmacology, 2008)

Prehibernating aggregations of Polistes dominulus: an occasion to study early dominance assessment in social insects - Leonardo Dapporto; Elisabetta Palagi; Alessandro Cini; Stefano Turillazzi (The Science of Nature, 2006)